2020
DOI: 10.1039/d0cp01498b
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase reactions of iodide and bromide anions with ozone: evidence for stepwise and reversible reactions

Abstract: Ion-trap mass spectrometry maps the discrete steps in the reaction of I− and Br− with gaseous ozone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 29 publications
3
33
0
Order By: Relevance
“…The former is reported to be more sensitive and less dependent on water vapour concentrations but less specific, with large and highly variable background signals potentially arising from trace gases such as NO 3 , ClONO 2 and BrONO 2 . Despite this, night-time N 2 O 5 has been monitored in ambient air (as NO 3 − ) using I − reactant ions, showing reasonable agreement with optical methods (Slusher et al, 2004;Dubé et al, 2006;Chang et al, 2011).…”
Section: Introductionmentioning
confidence: 76%
“…The former is reported to be more sensitive and less dependent on water vapour concentrations but less specific, with large and highly variable background signals potentially arising from trace gases such as NO 3 , ClONO 2 and BrONO 2 . Despite this, night-time N 2 O 5 has been monitored in ambient air (as NO 3 − ) using I − reactant ions, showing reasonable agreement with optical methods (Slusher et al, 2004;Dubé et al, 2006;Chang et al, 2011).…”
Section: Introductionmentioning
confidence: 76%
“…In the gas phase, Ireacts with O3 in a stepwise process first producing IO -, with subsequent reaction steps with O3 to form IO2 -+ O2 and ultimately IO3 -+ O2 [7][8][9][10] . The overall rate limiting step in the formation of IO3is the first step, I -+ O3 , while the subsequent steps involving IOand IO2occur with high efficiency (91% and 84% of the collision rate, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Initial experiments by Williams et al showed that I − will cluster with O 3 , forming IO 3 − ; however, because of the reaction rate being below their detection limit 9 the formation of IO − from I − + O 3 was not detected. 10 In the gas phase, I − reacts with O 3 in a stepwise process first producing IO − , with subsequent reaction steps with O 3 to form IO 2 − + O 2 and ultimately IO 3 − + O 2 .…”
mentioning
confidence: 99%
“…Interestingly, the slow reversible reactions of IO − and IO 2 − (but not IO 3 − ) with dioxygen have also been studied with the latter case regenerating IO − . 9 Although the reaction kinetics and nucleation processes of these anion intermediates are becoming better characterized, there remains a lack of information on the photochemistry of these atmospheric anions, including the simplest iodine oxide anion, IO − . The electron binding energies of the iodine oxides have been measured and suggest that IO − (eBE = 2.3805 eV, 520 nm) 13−15 and IO 2 − (eBE = 2.575 eV, 481.5 nm) 14,16 but not IO 3 − (eBE = 4.70 eV, 263.8 nm) 16 may undergo photodetachment within the actinic window of the lower stratosphere, 17 presenting a pathway to the corresponding neutral radicals.…”
mentioning
confidence: 99%
See 1 more Smart Citation